Α Kinetic Study of Humate Extraction from Carbonaceous Waste using Alkaline Reagents - Kambatyrov, Maksat; Abdurazova, Perizat; Nazarbek, Ulzhalgas; Raiymbekov, Yerkebulan (Engineering, Technology & Applied Science Research, 2025)
The purpose of this study was to investigate the leaching process of coal waste under various alkaline reagents (NaOH, KOH, and NH4OH) to obtain humate compounds, and assess the impact of concentration and temperature on reaction kinetics. The Scanning Electron Microscopy with Energy Dispersive X-ray analysis (SEM-EDX), X-ray Diffraction (XRD), and Fourier-Transform Infrared spectroscopy (FTIR) methods were employed to study the physicochemical properties of carbon-containing waste. The Diffusion-Controlled Model (DCM) and Kramers Model (KM) were applied to calculate the reaction rate constants and activation energies. The results demonstrated that KOH exhibited the highest efficiency with a pH value of 13.59 at a 10 % concentration and 60 °C, while the activation energy for NaOH, KOH, and NH4OH ranged from 11.90 to 15.60 kJ/mol. These findings focus on temperature impact and confirm the applicability of the proposed models for analyzing and predicting the leaching processes of coal waste.